BED domain‐containing NLR from wild barley confers resistance to leaf rust. Issue 6 (6th March 2021) - Chen, Chunhong; Jost, Matthias; Clark, Bethany; Martin, Matthew; Matny, Oadi; Steffenson, Brian J.; Franckowiak, Jerome D.; Mascher, Martin; Singh, Davinder; Perovic, Dragan; Richardson, Terese; Periyannan, Sambasivam; et al.
Summary: Leaf rust, caused by Puccinia hordei, is a devastating fungal disease affecting barley ( Hordeum vulgare subsp. vulgare ) production globally. Despite the effectiveness of genetic resistance, the deployment of single genes often compromises durability due to the emergence of virulent P. hordei races, prompting the search for new sources of resistance. Here we report on the cloning of Rph15, a resistance gene derived from barley's wild progenitor H. vulgare subsp. spontaneum . We demonstrate using introgression mapping, mutation and complementation that the Rph15 gene from the near‐isogenic line (NIL) Bowman +  Rph15 (referred to as BW719) encodes a coiled‐coil nucleotide‐binding leucine‐rich repeat (NLR) protein with an integrated Zinc finger BED (ZF‐BED) domain. A predicted KASP marker was developed and validated across a collection of Australian cultivars and a series of introgression lines in the Bowman background known to carry the Rph15 resistance. Rph16 from HS‐680, another wild barley derived leaf rust resistance gene, was previously mapped to the same genomic region on chromosome 2H and was assumed to be allelic with Rph15 based on genetic studies. Both sequence analysis, race specificity and the identification of a knockout mutant in the HS‐680 background suggest that Rph15‐ and Rph16 ‐mediated resistances are in fact the same and not allelic as previously thought. The cloning of Rph15 now permits efficient gene deployment and the production of resistance gene cassettes for sustained leaf rust control.